The “crab sign”: an imaging feature of spinocerebellar ataxia type 48 - Cocozza, Sirio; Pontillo, Giuseppe; De Michele, Giovanna; Perillo, Teresa; Guerriero, Elvira; Ugga, Lorenzo; Salvatore, Elena; Galatolo, Daniele; Riso, Vittorio; Saccà, Francesco; Quarantelli, Mario; Brunetti, Arturo (Neuroradiology, 2020)
Purpose A new form of autosomal dominant hereditary spinocerebellar ataxia (SCA) has been recently described (SCA48), and here we investigate its conventional MRI findings to identify the presence of a possible imaging feature of this condition. Methods In this retrospective observational study, we evaluated conventional MRI scans from 10 SCA48 patients (M/F = 5/5; 44.7 ± 7.8 years). For all subjects, atrophy of both supratentorial and infratentorial compartments were recorded, as well as the presence of possible T2-weighted imaging (T2WI) signal alterations. Results In SCA48 patients, no meaningful supratentorial changes were found, both in terms of volume loss or MRI signal changes. Atrophy of the cerebellum was present in all cases, involving both the vermis and the hemispheres, but particularly affecting the postero-lateral portions of the cerebellar hemispheres. In all patients, with the exception of only one subject (90.0% of the cases), a T2WI hyperintensity of both dentate nuclei was found. The association of such signal alteration with the pattern of cerebellar atrophy resembled the appearance of a crab (“crab sign”). Conclusion Our findings suggest that SCA48 patients are characterized by cerebellar atrophy, mainly involving the postero-lateral hemisphere areas, along with a T2WI hyperintensity of dentate nuclei. We propose that the association of such signal change, along with the atrophy of the lateral portion of the cerebellar hemispheres, resembled the appearance of a crab, and therefore, we propose the “crab sign” as a neuroradiological sign present in SCA48 patients.